IC 9111 Availability Of Rare-Earth, Yttrium, And Related Thorium Oxides-Market Economy Countries - A Minerals Availability Appraisal - T. F. Anstett (The National Institute for Occupational Safety and Health (NIOSH), 1986)
The Bureau of Mines estimated the potential availability of rare-earth oxides (EtEO), including yttrium, and thorium, which is also contained in the rare-earth bearing minerals monazite and bastnasite, from 38 'properties in market economy countries (MEC's). Only nine of the properties evaluated produce or would produce REO as the primary product; the others contain REO as a byproduct, chiefly from mineral sands operations recovering rutile, ilmenite, and zircon. Nearly 77% (2,578,000 mt) of the total 3,355,000 mt of recoverable RE0 evaluated is from producing properties. It is estimated that 21% (705,000 mt) of this total is from properties that could not realize a positive rate of return at the January 1984 market prices for the recovered commodities. At production capacities assumed for this evaluation, the amount of RE0 potentially available from producers ranges from an estimated 46,500 mt in 1986, to a peak of 50,900 mt in 1992, to 49,900 mt by the year 2000. Total MEG production in 1984 was estimated at 40,700 mt. Assuming demand does not increase sharply, producing properties can continue to fulfill overall REO demand through at least the end of this century.